There Is A Beauty in the Door(way) of Flying Daggers. Issue 2 (1st September 2005) - Chen, Ya-chen
This article begins with my interpretation of possible interrelations between the film and the above-mentioned poem that begins with 'beifang you jiaren' ('There is a beauty in the North'; my own English translation). In Li Yannian's poem, the 'jiaren' (the beauty) is compared with the 'cheng' (the city or castle) and 'guo' (the nation or country) and thus objectified. Li Yannian inadvertently turns the jiaren into a scapegoat if the country and citizens are not taken good care of. Zhang Yimou revises the destiny of the jiaren by permitting her to speak her mind and decide her fate.